EFEKTIFITAS MODEL PEMBELAJARAN PROJECT BASE LEARNING DALAM KONTEKS BLEDED LEARNING UNTUK MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN PENCAK SILAT MAHASISWA - I Gede Suwiwa (Universitas Pendidikan Indonesia, 2021)
This study aimed to improve student knowledge and skills in Pencak Silat by applying project-based learning in a blended learning setting. The research method uses an experimental with a quasi-experimental design, involving a control group and an experimental group. The study participants involved 70 college students divided into a control and random group using a random sampling technique. The data in the study were collected by utilizing a questionnaire—data analysis using Paired Sample T-test method. The study showed that the Project-Based Learning model in a blended learning setting improves student knowledge and skills in the Pencak Silat learning process. It can be seen from the increase that occurred in the control and experimental groups. Thus, learning Pencak Silat through Project-Based Learning in a blended learning setting is an effective alternative to improving student knowledge and skills in Pencak Silat.